(untitled) (Mugda Medical College Journal, 2023)
A 20-year old male patient reported in the outpatient department of Shaheed Suhrawardy Medical College Hospital, Dhaka, Bangladesh, with the complaints of body aches along with pain in the upper and lower limbs for several years. He also gave history of previous hospitalization for the same reason. He also had complaints of failure to thrive in his adolescence. However, he was treated as a case of polyarthritis in his previous admission in the district hospital. On clinical examination, he was found to have short stature, low-weight, peculiar face, prominent forehead, receding jaw and partial dysplasia of the terminal phalanges. He was sent for radiological investigations in the Department of Radiology & Imaging of the same hospital. Plain radiograph of his skull showed brachycephaly with wide sutures and persistent fontanelles with sclerotic changes in the base of skull and orbital rims. The angle of the mandible was obtuse, and the maxilla was found hypoplastic. Lumbar region showed ‘spool-shaped’ vertebral bodies with quite prominent anterior defects; bones had sclerotic changes. Both hands had acro-osteolysis of distal phalanges of thumb, index, middle and ring fingers (both right and left sides) along with irregular distal fragments; bones were sclerotic, too. Those features were consistent with pycnodysostosis. The patient was kept admitted into the hospital and treated accordingly. After obtaining a written informed consent, he was presented as a special case in clinical seminar. Mugda Med Coll J. 2022; 5(2): 110-113